2016
DOI: 10.1051/swsc/2016009
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry-emission coupled model for Europa and Ganymede

Abstract: In the frame of the JUICE mission, preliminary studies of the Jupiter's icy moons, such as Ganymede and Europa, are mandatory. The present paper aims at characterizing the impact of the solar UV flux and its variability on their atmospheres. The solar UV radiation is responsible for the photoionization, photodissociation, and photoexcitation processes within planetary atmospheres. A 1-D photoabsorption model has been developed for different observational geometries, on the basis of a neutral atmospheric model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Both TSI and SSI measurements are of primary interest for space weather and space climate studies. The planetary climate response to the solar irradiance is sensitive to the 11-year cycle, when considering the Earth (Egorova et al 2004;Ermolli et al 2013) as well as planetary objects such as the jovian icy moons (Cessateur et al 2016). The 27-day solar modulation also has a strong impact on mesospheric neutral species such as hydroxyl (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Both TSI and SSI measurements are of primary interest for space weather and space climate studies. The planetary climate response to the solar irradiance is sensitive to the 11-year cycle, when considering the Earth (Egorova et al 2004;Ermolli et al 2013) as well as planetary objects such as the jovian icy moons (Cessateur et al 2016). The 27-day solar modulation also has a strong impact on mesospheric neutral species such as hydroxyl (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…UV radiation using Hg lamps has been considered in only a few studies that considered the production of organics from HCN/cyanide as main reactant (Abelson, 1966;Mizutani et al, 1975;Hartig and Getoff, 1980;Ritson and Sutherland, 2012;Ruiz-Bermejo et al, 2013a). The amount and type of UV radiation that arrives at a predetermined planetary zone depend on several factors (the dispersion, transmittance, and albedo of the environment), and it is an important constraint to take in consideration in the astro/exobiological exploration of the icy objects of solar systems (Cessateur et al, 2016). Ice is a highly dispersive environment and reflects UV radiation; thus, the presence of an icy layer notably reduces the UV radiation incident on the liquid water of the ocean, and it has been demonstrated that sea ice acts as a photochemical microreactor, where 85% of the reactions are produced in the upper zone of the icewater column (King et al, 2005).…”
Section: Introductionmentioning
confidence: 99%